Isolation, identification and antibiogram profile of bacteria isolated from dental caries patients of Mymensingh district of Bangladesh - Borty, Shuvho Chakra; Hafiz, Khandakar Musabbir Bin; Ali, Md Mortuza; Begum, Khadiza; Ahammed, Tanvir; Monir, Md Shirajum; Islam, Md Alimul (Asian Journal of Medical and Biological Research, 2015)
This study was carried out for the evaluation of causative agents of dental plaques which leads to dental caries. A total of 76 samples collected from the dental caries patients of various age and sex were processed on different bacterial isolation media like Tryptose Soya Agar, Nutrient Agar, and MacConkey Agar. Total viable count of bacteria was ranged from 0.8×105 to 2.9×105. Out of total 184 isolates bacterial species were Streptococcus mutans (28.80%), Streptococcus mitis (23.91%), Staphylococcus aureus (28.26%) and Streptococcus salivarius (19.02%). The biochemical properties of the isolates were tested according to Bergeys Manual of Systematic Bacteriology and UK Standards for Microbiology Investigation. Antibiotic Susceptibility testing of different species of bacteria were performed according to Kirby Bauer disc diffusion method on Muller Hinton Agar by using commercial antibiotic discs. Effect of the bacterial isolates on different age groups was studied where the age group of 26 to 35 years was found to have highest prevalence (32.60%) of infection while the lowest prevalence (10.86%) of infection was seen in the group of below 15 years of age. A relative study was also performed on caries patients according to their economic status and gender where Higher Middle Economic Class was in highest percentage (35.32%) of infection. Different species of bacteria showed various sensitivity patterns to several kinds of antibiotics. Regular use of tooth paste containing triclosan and fluoride may be beneficial for prevention of dental caries instead of using antibiotics presented in this study. Asian J. Med. Biol. Res. June 2015, 1(2): 244-253